Political and Metaphysical: Reflections on Identity, Education, and Justice - Bialystok, Lauren (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
John Rawls (1985) famously argued that social justice ought not to concern itself with the metaphysical disputes that separate us as groups and individuals. Identity is supposed to be irrelevant to the deliberations of free and equal citizens. Since the recent turn toward right-wing populism, renewed attention has been devoted to the place of identity in contemporary Western societies. In this paper, building on key philosophical accounts of identity, I argue against both political liberalism’s confidence in identity-blind justice and some contemporary conceits of social justice education, according to which identity is the beginning and end of normative judgments. In the first section I show how identity appeals to a notional horizon of authenticity against which specific claims are adjudicated, and which takes on normative significance in its own right. I then consider two examples of recent controversies in Canada over the meaning of Indigenous identity and gender identity, respectively, which reveal latent tensions in the pursuit of social justice. In the final section I sketch the implications of these tensions for school-based education and the role of education in advancing identity talk more generally.